Integral Estimates for the Potential Operator on Differential Forms. (30th January 2013) - Johnson, Casey; Ding, Shusen
Abstract : We develop the local inequalities with new weights for the potential operator applied to differential forms. We also prove the global weighted norm inequalities for the potential operator in averaging domains and explore applications of our new results.